PENGARUH SUHU TERHADAP DIFERENSIAL LEUKOSIT SERTA KADAR MALONDIALDEHIDE (MDA) BURUNG PUYUH (Coturnix coturnix Japonica) - Maheshwari, Hera; Sasmita, Annissa Nuridfi; Farajallah, Achmad; Achmadi, Pudji; Santoso, Koekoeh (Bioma, 2017)
The main problem in tropical poultry farming that often happens is a high mortality rate. Deaths occurrance mostly by heat stress, a condition which is caused by high temperature ( > 28 ° C). Prolonged heat stress was given to 24 quails grouped in four groups: A (39 ° C), B (41 ° C), C (43 ° C) and D (45 ° C). Provision of heat stress was done when the quails were 2 days old. Blood sampling was performed at the age of 6 weeks. Overall, there was an increase in the number of white blood cell, heterophile, eosinophil, monocyte, the ratio between heterophyll and lymphocyte and malondialdehyde (MDA) levels in all treatment groups. While the number of lymphocytes decreased in all treatment groups. Basophils had a significant increase in group C, but there was a decrease in group B and D decreased from control. This indicates that maintenance above temperature > 25 ° C can cause oxidative stress due to heat stress in quail.